Nurse Staffing and Coronavirus Infections in California Nursing Homes. (August 2020) - Harrington, Charlene; Ross, Leslie; Chapman, Susan; Halifax, Elizabeth; Spurlock, Bruce; Bakerjian, Debra
In the United States, 1.4 million nursing home residents have been severely impacted by the COVID-19 pandemic with at least 25, 923 resident and 449 staff deaths reported from the virus by June 1, 2020. The majority of residents have chronic illnesses and conditions and are vulnerable to infections and many share rooms and have congregate meals. There was evidence of inadequate registered nurse (RN) staffing levels and infection control procedures in many nursing homes prior to the outbreak of the virus. The aim of this study was to examine the relationship of nurse staffing in California nursing homes and compare homes with and without COVID-19 residents. Study data were from both the California and Los Angeles Departments of Public Health and as well as news organizations on nursing homes reporting COVID-19 infections between March and May 4, 2020. Results indicate that nursing homes with total RN staffing levels under the recommended minimum standard (0.75 hours per resident day) had a two times greater probability of having COVID-19 resident infections. Nursing homes with lower Medicare five-star ratings on total nurse and RN staffing levels (adjusted for acuity), higher total health deficiencies, and more beds had a higher probability of having COVID-19 residents. Nursing homes with low RN and total staffing levels appear to leave residents vulnerable to COVID-19 infections. Establishing minimum staffing standards at the federal and state levels could prevent this in the future.